A comprehensive review of parabolic trough solar collectors equipped with turbulators and numerical evaluation of hydrothermal performance of a novel model. (June 2021) - Shahzad Nazir, Muhammad; Shahsavar, Amin; Afrand, Masoud; Arıcı, Müslüm; Nižetić, Sandro; Ma, Zhenjun; Öztop, Hakan F.
Highlights: Critical review of previous studies on the performance of PTSCs with turbulators. Comparison of previous studies on PTSCs using Nuav /Nuav, 0, fav / fav, 0 and PEC. Identifying the most optimum turbulators. Combination of optimum geometries of corrugated channels and channels with obstacles. Introducing a novel and optimal PTSC. Abstract: Absorber tube in parabolic trough concentrating systems is located at the location of the focal line and a fluid passes through it, the temperature of which increases due to receiving heat from sunlight. The more heat the fluid can absorb from the concentrated solar energy, the better the performance of the system. Since turbulators can be used in the absorber tube for this purpose, a lot of experimental and numerical research have been done on the performance of parabolic trough collectors equipped with various turbulators. In this study, the most important findings of these studies are presented and then, Nusselt number ratio, mean friction factor ratio, and thermal–hydraulic performance evaluation criterion are used to compare the hydrothermal performance of the systems. After reviewing previous researches and identifying advantages and disadvantages of each turbulator, a novel parabolic trough collector equipped with a turbulator is introduced and its hydrothermal performance is evaluated through simulation. The outcomes revealed that the ribbed absorber tube and the concentric rod insert are the most optimum turbulators. In addition, the parabolic trough collector equipped with a combination of corrugated channel and obstacle has a much better hydrothermal performance than the collectors using each of these turbulators separately.